แนวทางการจัดกิจกรรมการเรียนรู้ตลอดชีวิตเพื่อส่งเสริมความเป็นเมืองแห่งการอ่าน - พันธ์นุวัฒน์ บุษบา (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
This future research study applied the Delphi Technique. The purposes of the study were to 1) analyze the current conditions of components and lifelong learning activities of the city of reading, and 2) propose guidelines of organizing lifelong learning activities to enhance being the city of reading. The data were gathered and analyzed by using content analysis of different research studies both in Thailand and foreign countries, the open-ended interview form of three reading communities, and the Delphi Technique questionnaire given to ten experts in the field. The results were as follow. 1. The components and lifelong learning activities of the city of reading included five main components: the principles and policies, the development processes, the lifelong learning activities, the learning resources, and the learning network. Each components and lifelong learning activities comprised of the sub-components and activities to enhance being the city of reading. 2. The proposed guidelines of organizing lifelong learning activities to enhance being the city of reading included five key guidelines: 1) the principles and policies: principles were network participation, continuous reading promotion, and etc.; and policies were to create awareness about importance of reading and lifelong learning, to develop the libraries as a center of reading culture, and to promote the ways to access the books; 2) the development processes: to promote reading activities to serve the condition/context of each area, to develop learning resources and qualified staff who are able to provide reading services and activities, to promote reading habits for people in the society; 3) the lifelong learning activities: the city of reading should have variety of activities, such as Book Start, One City One Book, and etc.; 4) the learning resources: the prices of several books and other learning resources should be reasonable and cheap, and the city should provide learning places/spaces appropriately, and improve the information technology systems; and 5) the learning networks: all sectors in the society (e.g., government agencies, private sectors, educational institutions, and family) should promote reading activities to foster the reading habits. Therefore, it is hoped that the above mentioned guidelines of organizing lifelong learning activities to enhance being the city of reading will be useful for every city toward enhancing the city of reading.